PERSPEKTIF ALKITAB MENGENAI PERAN KELUARGA SEBAGAI BASIS PENDIDIKAN AGAMA KRISTEN - Mersiani Rerung Datte; Elis Elis; Yasri Gonggang Lolok; Fritsilia Yuni Ba’si; Alvin Palute Dase’ (ADIBA : JOURNAL OF EDUCATION, 2023)
This research aims to investigate the biblical perspective regarding the role of the family as the primary foundation for Christian religious education. The family plays a crucial role in shaping the faith and morality of the younger generation within the context of Christianity. By understanding the Bible's viewpoint on the family's role in Christian religious education, we can gain deeper insights into how families can effectively fulfill this responsibility. The research will employ an exploratory method of analyzing biblical texts, with a focus on relevant verses pertaining to the family's role in Christian religious education. Additionally, this study will utilize Christian theological literature and secondary sources that support the analysis of the Bible. The anticipated outcomes of this research are expected to contribute to our understanding of how the Bible regards the family as a fundamental institution for education within the realm of Christianity. The practical implications of this research can serve as a guide for the practice of Christian religious education within both family and church settings.